Use of rainwater in urban areas and storm warter run-off quality management: environmental and economic aspects - Біткова, Т. В.; Ричак, Н. Л.; Гричаний, О. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The paper considers the reasons for deepening current problems of the surface waters and control of surface wastewater quality in the cities of Europe and the world; the analysis of climatic and other natural factors affecting the assessment of the feasibility of rainwater management projects in a particular city (by the case of Kharkiv) is carried out; the results of the study on the pressure on water bodies brought by the surface waters within the urban landscape geo-system are provided; ecological assessment of the water body is made. The analysis of long-term statistical data and review of the current literature on the subject indicates that there is a trend towards the increase in precipitation in European cities with a moderate climate and in some cities with a tropical one. Over the last 10 years extreme erratic intensity of rainfall, both in terms of monthly precipitation in the warm half-year (May–October), and in the total monthly and seasonal number of rainy days has become typical for Kharkiv. Moreover, there is a change in the precipitation patterns – a decrease in the number of moderate rains and an increase of thunderstorms, showers and hail. Applying modern methods, the amount of surface water in the city is estimated, taking into account the percentage of the city’s territory densely covered with water. The quality of surface waters is determined by means of chemical analysis; the pressure on water bodies through unorganized surface run-off surface runoff from the urban territory is determined and assessed. The article presents an overview of successful urban projects of rainwater harvesting, its retention and practical usage, taking into account the sources of financing and offers measures and recommendations on implementing blue economy projects in the conditions of some particular city.